DINAMIKA STRUKTUR KEPEMILIKAN DAN KEBERLANJUTAN LABA: STUDI EMPIRIS PERUSAHAAN TRANSPORTASI DAN LOGISTIK DI BEI - Marbun, Melia Rumata; Wibowo, Agus Satrya; Setiawan, Ricky Yunisar (LPPM Universitas Bina Bangsa, 2025)
This study explores the complex dimension of profit persistence as a fundamental construct that reflects a company's capacity to maintain stability and profit predictability over a given period. The focus of the investigation is focused on the structural analysis of ownership – including institutional, managerial, and concentration ownership – as well as their implications for profit persistence in the context of the transportation and logistics sector in Indonesia. Using the population of 29 companies listed on the Indonesia Stock Exchange (www.idx.co.id) during the 2021-2023 period, the study applied a purposive sampling technique that produced a representative sample of 9 companies. The analytical methodology adopts a multiple linear regression approach through the SPSS instrument, which allows for a comprehensive investigation of the dynamics of intervariables. Empirical findings reveal significant patterns: although simultaneously ownership structures have no substantive effect on profit persistence, ownership concentration is shown to make a positive and significant contribution, while institutional and managerial ownership do not show a statistically significant effect on firms' profit persistence